2023
DOI: 10.3390/antiox12030736
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D from UV-Irradiated Mushrooms as a Way for Vitamin D Supplementation: A Systematic Review on Classic and Nonclassic Effects in Human and Animal Models

Abstract: Recent literature has shown that vitamin D, in addition to its well-known activity on the skeleton, has many positive effects on health. Unfortunately, it is not easy to meet intake needs solely with food. Mushrooms could provide a valid way to achieve this goal, because they are one of the few sources of vitamin D. The aim of this systematic review was to summarize what has been reported in the literature on the treatment of animal and human models with irradiated commercial mushrooms, with particular attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Overall, the coating improved the shelf life of the coated mushrooms. Rondanelli et al [31] reported that Coated mushrooms had less mass loss and color change, and had better texture up to 14 days. Overall, the coating improved the shelf life of the coated mushrooms but had less effect on the microbial community Pleșoianu et al [32] who has also reported similar results of weight loss of mushrooms during storage has attributed to moisture evaporation and respiration.…”
Section: Quality Assessment Of Edible Polysaccharide-coated Agaricus ...mentioning
confidence: 99%
“…Overall, the coating improved the shelf life of the coated mushrooms. Rondanelli et al [31] reported that Coated mushrooms had less mass loss and color change, and had better texture up to 14 days. Overall, the coating improved the shelf life of the coated mushrooms but had less effect on the microbial community Pleșoianu et al [32] who has also reported similar results of weight loss of mushrooms during storage has attributed to moisture evaporation and respiration.…”
Section: Quality Assessment Of Edible Polysaccharide-coated Agaricus ...mentioning
confidence: 99%
“…While meta-analyses have shown that vitamin D 3 is more effective than vitamin D 2 in increasing total vitamin D status, these relationships appear to be modified by both BMI and baseline vitamin D status ( 59 ). A 2023 systematic literature review identified that vitamin D 2 from UV-exposed mushrooms (from 8.8 μg/day) consistently increased serum levels of vitamin D 2 compared to placebo ( 60 ). However, there was no change in total vitamin D levels in most studies, possibly explained by the concomitant decrease in vitamin D 3 levels in 50% of studies.…”
Section: Introduction: Vitamin D Deficiency Is a Global Problemmentioning
confidence: 99%